Short-term neurodevelopmental outcomes in neonates with perinatal asphyxia: Experience of a tertiary care hospital in Bangladesh - Kamal, MA; Haque, Emdadul (Journal of Shaheed Suhrawardy Medical College, 2025)
Background: Perinatal asphyxia is one of the leading causes of neonatal mortality, ranking third after sepsis and prematurity. It is also a major contributor to childhood morbidity. However, the most concerning consequence is its impact on the brain, which can lead to long-term neurological impairment. Objective: The objective of this study was to observe the short-term neurodevelopmental outcomes in neonates affected by perinatal asphyxia. Methodology: This study was a prospective cohort study conducted at department of neonatology, Bangladesh Shishu Hospital & Institute (BSH&I) from January 2023 to December 2023; Total 429 newborn were screening among them 46 newborns with perinatal asphyxia fulfilling the inclusion criteria were included in the study. Inclusion criteria were; Term (37-41 week gestational age) and late preterm (34-36 week gestational age) newborns. Newborns satisfying the American Academy of Pediatrics/American College of Obstetrician criteria of perinatal asphyxia. Exclusion criteria were; Early preterm and Babies with an antenatally diagnosed significant congenital malformation or clinically suspected TORCH infection. Results: Among 429 newborn babies 46 were found perinatal asphyxia and their prevalence rate was 10.7%. Regarding hospital outcomes, 39(84.8%) were discharged, while 7(15.2%) were expired. The duration of hospital stay varied, with 10 newborns (21.7%) staying for less than 7 days, 22 (47.8%) staying between 7-14 days, and 14 (30.4%) staying for more than 14 days. A significant association was found between the HIE stage and hospital outcomes (p<0.05). In majority cases (87.5%) low HINE scores were predominantly observed in HIE Stage III, while high scores were associated with HIE Stage I. Conclusion: There is a significant association between the severity of Hypoxic-Ischemic Encephalopathy (HIE) and both neurological outcomes and hospital discharge status. Infant who presented with more severe brain injury at birth tended to have high risk of development of significant neurological impairment. J Shaheed Suhrawardy Med Coll 2024; 16(1): 28-32